2018
DOI: 10.1111/sms.13291
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and parasympathetic reactivation in rescue interventions: The effect of the breathing apparatus

Abstract: This study aimed to assess the effect of wearing a breathing apparatus during a simulated rescue intervention on psychophysiological responses and parasympathetic reactivation of firefighters. Thirty-four firefighters participated in this study which consisted of four experimental sessions conducted randomly: a maximal fitness test and three rescue interventions performed (a) with personal protective clothing (PPC); (b) with PPC and the full self-contained breathing apparatus (SCBA), including cylinder, full-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 46 publications
(143 reference statements)
3
50
0
1
Order By: Relevance
“…Selected publications included males only in 11 studies, both males and females in seven studies and the gender distribution was not reported in three studies. Seven tactical subpopulations were represented; general law enforcement officers ( 32 , 33 ), Army ( 27 , 29 , 31 , 34 36 , 46 ), Defense Force trainees ( 37 ), Naval cadets ( 38 ), Army Ranger trainees ( 39 ) firefighters/rescue personnel ( 28 , 30 , 40 , 41 , 43 , 45 ), and Air Force fighter pilots ( 42 ). Specifically, the Army personnel were members of either the US, Brazilian or Spanish militaries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Selected publications included males only in 11 studies, both males and females in seven studies and the gender distribution was not reported in three studies. Seven tactical subpopulations were represented; general law enforcement officers ( 32 , 33 ), Army ( 27 , 29 , 31 , 34 36 , 46 ), Defense Force trainees ( 37 ), Naval cadets ( 38 ), Army Ranger trainees ( 39 ) firefighters/rescue personnel ( 28 , 30 , 40 , 41 , 43 , 45 ), and Air Force fighter pilots ( 42 ). Specifically, the Army personnel were members of either the US, Brazilian or Spanish militaries.…”
Section: Resultsmentioning
confidence: 99%
“…For the Fire/Rescue personnel, members were serving in French, Brazilian, Finnish, Portuguese, or South Korean communities. A total of nine countries were represented: USA ( 27 , 32 , 33 ), Spain ( 29 , 31 , 34 , 35 ), Brazil ( 30 , 36 , 42 , 46 ), South Africa ( 37 ), Norway ( 38 ), France ( 28 , 39 ), Finland ( 40 , 41 ), Portugal ( 43 , 44 ), and South Korea ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Technological development is driving an increasing interest in the monitoring of workers during their activities, with the aim to improve health, well-being, and safety. Various multiparameter wearable devices measuring fR have been developed and tested with the aim of monitoring workers facing high levels of psychophysiological stress [17,18]. Monitoring fR during working activities is of great value because fR is sensitive to cognitive load, emotional stress, environmental challenges, pain, and discomfort, among other factors [3,19].…”
Section: Introductionmentioning
confidence: 99%